The Study of Text and Hypertext Dimensions of the Works of Ahmad Khan Shahrokhi: One of the Renowned Masters of Kerman Carpet Designing - Kermani, Iman Zakariaee; Gooki, Maryam Sultani (Journal of History Culture and Art Research, 2017)
Artistic cultural honors could be considered as one of the most important components in cultural identity and identifying them could pave the way for cultural development. Recognition of the honors and studying their role and position in ethnical cultures could be also considered as one of the strategies to promote cultural identity. In art and culture of Kerman, Carpet Art or industry has centuries-old history. The most important feature of Kerman Carpet is that it has been able to join cultural and political evolutions properly and represent the epistemological formations and common discourses on culture competently. The Guild System of Kerman Carpet has observed presence of numerous artistic dynasties, which the most indicator artists could be in Shahrokhi Family. Among the artists of Shahrokhi Family, in addition to Mohsen Khan and Hassan Khan, Ahmad Khan has also a special position. This study has tended to use descriptive-analytical method to discuss on some artistic and personality indicators of Ahmad Khan Shahrokhi and answer the main question that what is the role and position of this artist in traditional art of Kerman Carpet? The results obtained from this study could be analysis of some brilliant works of Ahmad Khan. Through analyzing and stylistic investigation of these works and expressing some text and hypertext dimensions of these works, the role and position of this artist is specified. The artist has been considered as a pattern, developer and pioneer due to his personality and artistic traits.